(E)-4-Hydroxy-N '-(2-hydroxy-4-methoxybenzylidene)benzohydrazide N,N-dimethylformamide solvate - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The Schiff base molecule of the title compound, C(15)H(14)N(2)O(4)-C(3)H(7)NO, adopts a trans configuration with respect to the C=N double bond; the Schiff base itself is nearly planar (r. m. s. deviation 0.20 angstrom). The amido N atom is a hydrogenbond donor to the dimethylformamide solvate molecule. One of the hydroxy groups forms an intramolecular hydrogen bond to the N atom of the C N double bond, whereas the other forms an intermolecular hydrogen bond to the carbonyl group.